1998
DOI: 10.1164/ajrccm.158.3.9802031
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal Epinephrine Increases Alveolar Liquid Clearance in a Canine Model of Neurogenic Pulmonary Edema

Abstract: Case reports of neurogenic pulmonary edema (NPE) often indicate that the edema resolves quickly. Because plasma epinephrine concentration may be elevated in NPE, and epinephrine has been shown to increase the rate of alveolar liquid clearance (ALC), we determined if ALC was increased in a canine model of NPE produced by the intracisternal administration of veratrine. ALC was determined by instilling autologous plasma into a lower lung lobe and using the increase in instillate protein concentration after 4 h to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
51
3
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 33 publications
3
51
3
1
Order By: Relevance
“…This damage may be reversible with time. Animal studies have shown that high levels of circulating epinephrine, which are released by the adrenals for some time after the initial sympathetic discharge, can increase alveolar fluid clearance via b 2 -adrenergic stimulation of type II alveolar epithelial cells and lead to recovery from NPE (45,46). This could be enhanced in humans with aerosolized b 2 -adrenergic treatment (47).…”
Section: Discussionmentioning
confidence: 99%
“…This damage may be reversible with time. Animal studies have shown that high levels of circulating epinephrine, which are released by the adrenals for some time after the initial sympathetic discharge, can increase alveolar fluid clearance via b 2 -adrenergic stimulation of type II alveolar epithelial cells and lead to recovery from NPE (45,46). This could be enhanced in humans with aerosolized b 2 -adrenergic treatment (47).…”
Section: Discussionmentioning
confidence: 99%
“…can increase the capacity of the alveolar epithelium to remove alveolar edema fluid in septic shock, hypovolemic shock, and neurogenic injury (18,30,35,36). However, the effect of endogenous catecholamines in the presence of severe acute bacterial pneumonia on alveolar fluid clearance and lung fluid balance has not been well studied.…”
Section: Discussionmentioning
confidence: 99%
“…EARLIER EXPERIMENTAL WORK established that elevated endogenous epinephrine levels can increase the capacity of the alveolar epithelium to remove alveolar edema fluid in the setting of septic or hemorrhagic shock (29,35,36) or after an acute neurogenic insult (18). However, the effects of endogenous ␤-adrenoceptor tone on lung fluid balance have not been studied in acute severe bacterial pneumonia, the most common cause of clinical acute lung injury (10).…”
mentioning
confidence: 99%
“…Although terbutaline increased pulmonary blood flow, this effect was not important, since control studies with nitroprusside, an agent that increased pulmonary blood flow, did not increase fluid clearance. Other studies have demonstrated that ␤-adrenergic agonists increased fluid clearance in rat (164), dog (28,191), guinea pig (258), mouse (121, 124, 155), as well as human lung (307,308). The presence of ␤ 1 -and ␤ 2 -receptors on alveolar type II cells has been demonstrated in vivo by autoradiographic and immunochemistry techniques (19,98,201).…”
Section: Upregulation Of Fluid Transport By Sodium-dependent Mechanismsmentioning
confidence: 94%